Bifidobacterium animalis subsp. lactis BB-12 Improves the State Anxiety and Sports Performance of Young Divers Under Stress Situations: A Single-Arm, Prospective Proof-of-Concept Study - Dong, Weizhong; Wang, Ying; Liao, Shuaixiong; Tang, Wei; Peng, Li; Song, Gang (Frontiers in Psychology, 2021)
Background: Athletes will increase their state anxiety under stress situations, which will lead to the decline of sports performance. The improvement of anxiety by probiotics has been reported, but there is a lack of research in the athlete population. The purpose of the current study is to explore the effectiveness of probiotics in improving athletes' state anxiety and sports performance under stress situations. Methods: We conducted this single arm study in Chongqing Institute of Sports Technology. In the 8-week study, 21 Chongqing young divers (mean age: 9.10 ± 1.80 ) were given probiotic Bifidobacterium animalis subsp. lactis BB-12 (1 × 109 CFU / 100 g) daily. The state anxiety and sports performance of athletes were measured before, during and after the intervention, and the gut microbiota of athletes was measured before and after the intervention. Results: The intervention results showed that cognitive state anxiety, somatic state anxiety and anxiety emotion were improved (cognitive: Z = -3.964, P < 0.001; somatic: Z = -3.079, P = 0.003; anxiety: Z = -2.973, P < 0.001), In terms of gut microbiota, the intervention did not change the gut microbial composition (such as α diversity and β diversity), but increased the abundance of Bifidobacteriaceae. At the eighth week, the performance of athletes under stress was significantly improved (2 = 7.88, P = 0.019). Limitations: First of all, due to the restriction of the number of subjects in this study, there was no control group. Secondly, although athletes' diet was recorded in this study, the influence of this factor on gut microbiota was not eliminated. Finally, the anxiety level of athletes in this study was obtained through self-report, lacking of physiological data in state anxiety. Conclusion: The results show that probiotics intervention can improve the state anxiety of athletes under stress situation, and improve the performance of athletes under stress situation.